Continuity and discontinuity in African traditional religion: The case of the Igbo of Nigeria - Ejizu, Christopher I. (Cahiers des religions africaines, 1984)
This essay discusses the present state of the traditional religion of the Igbo: many traditional Igbo beliefs have continued their life side by side with christian dogmas. (Bibl. Afric. Z8600779)